POLA PEMBERIAN ANTIBIOTIK DI ERA PANDEMI COVID-19 (STUDI KASUS DI RUMAH SAKIT NASIONAL DIPONEGORO) - Putra, Dominikus Evano; Pramudo, Setyo Gundi; Arkhaesi, Nahwa; Retnoningrum, Dwi (Medica Hospitalia : Journal of Clinical Medicine, 2021)
Background: Inappropriate use of antibiotics could increase the incidence of antibiotic resistance, hence increasing morbidity, mortality, and health cost. WHO has recommended to conduct a study of rational use of antibiotics in order to overcome this problem. Aim: To analyze the quality and quantity of antibiotic use in inpatient care facility at Diponegoro National Hospital (RSND). Methods: Quality and quantity assessment conducted by the use of DDD/100 patient–days and the Gyssens criteria. The study was conducted retrospectively at 86 patients’ medical records that were obtained by consecutive sampling method. Results: There were 141 antibiotics prescriptions from 86 medical records. Azithromycin, levofloxacin, and ceftriaxone were the most commonly used and had 48,12; 44,01; and 21,13 DDD/100 patient–days. By Gyssens crieteria, 35,4% of antibiotic usage was appropriate, 51,1% of antibiotic usage was inappropriate, and 13,5% no indication of the use of antibiotic. Based on the type of therapy, ADE 89,4% and ADET 10,6%. Conclusion: In terms of quantity, the most commonly used antibiotic was azithromycin. In terms of quality, 35,4% antibiotic were used appropriately according to Gyssens criteria. Keywords: Antibiotic usage; internal medicine; DDD/100 patient–days; Gyssens criteria